Features of the professional training of future technicians and mechanics in college - STADIYCHUK, Iryna; KUBITCKIY, Sergiy (Journal of Education, Technology and Computer Science, 2013)
The article presents the characteristics of professional training of future technicians and mechanics in Agrotechnical Colleges. Substantiated leading professional functions of future technicians and mechanics and the corresponding to them professional skills. It is shown specific formation of professional competences of future technicians and mechanics